Estudo teórico das propriedades estruturais, eletrônicas e ópticas do tetraborato de lítio (Li2B4O7) - Santos, Cledson dos (2014)
In present dissertation we studied theoretically the structural, electronic and optical properties of lithium tetraborate, Li2B4O7, an important material, frequently used as detector of radiation and neutrons. As a calculation tool we utilized first-principles Linear Augmented Plane Wave (LAPW) method, based on Density Functional Theory and implemented into WIEN2k computer code. Exchange and correlation effects within the electronic system were simulated by recently developed |Modified Becke Johnson| (mBJ) semi-local potential. The lattice parameters and atomic positions within the Li2B4O7 unit cell were computationally relaxed, and the resulting structure was found to agree well with the experimental one. Calculated electronic structure (band structure and density of states DOS) revealed the nature and magnitude of the band gap (indirect, 9,2 eV), as well as the orbital character of the bands around it. The valence band top consists predominantly of oxygen´s p-states, while the conduction band bottom is dominated by the p-states of boron which is trigonally coordinated with its neighboring oxygens (B(1)). The energies of principal peaks in the valence band DOS, as well as the calculated magnitude of the gap, are found to agree very well with experimental findings. Next, we calculated real and imaginary part of dielectric tensor of the Li2B4O7, as well as its refractive index. Analysis of imaginary part of dielectric tensor permitted us to interpret the optical absorption spectrum of the Li2B4O7 in terms of electronic transitions that occur between populated and empty electron states. The results revealed that absorption threshold starts at 9,2 eV approximately, and that the first absorption peak originates from electron transfer from the full O p-states to the empty B p-states within the trigonal, B(1)O3, structural motif. Refractive index is calculated for two directions of polarizations of incident light, parallel to the crystallographic axes a and c. It was concluded that the Li2B4O7 is optically anisotropic material. Calculated refractive indexes were compared to experimental ones, recorded in the wavelength range from 184 to 2325 nm, and it was found a good agreement between them. On the basis of present study we conclude that computationally efficient semi-local mBJ potential accurately describes the electronic and optical properties of the Li2B4O7.